EVALUASI PENGGUNAAN OBAT BEBAS DAN BEBAS TERBATAS - Kemal, Amir (Journal of Pharmacy Tiara Bunda, 2021)
Self-medication is part of the community's efforts to overcome minor illnesses by using over-the-counter drugs, limited over-the-counter medicines and mandatory pharmacy medicines without consulting a doctor first. This study was conducted to determine the evaluation of the use of over-the-counter and limited-free drugs in Cipayung village based on knowledge and rationality of drug use. Respondents were selected based on predetermined inclusion and exclusion criteria. Data were collected through interviews using a questionnaire that had been tested for validity and reliability. The number of respondents obtained were 110 respondents with consecutive sampling method from five pharmacies in Cipyaung Village, Cipayung District, Depok City. The data obtained from the results of filling out the questionnaire were collected and analyzed descriptively. Then coding is carried out on each answer by giving a certain score or value. Then the data are grouped according to their respective characteristics and displayed in tabular form. The results showed that the patient's level of knowledge was 37.3% classified as poor, 39.1% classified as moderate and 23.6% classified as good. The use of self-medication was 17.3% irrational and 82.7% rational. Based on the results of the study, it was found that the patient's level of knowledge was moderate with a percentage of 39.1%. While the rationality of self-medication is considered rational with a percentage of 82.7%.